2010
DOI: 10.2320/matertrans.mc200910
|View full text |Cite
|
Sign up to set email alerts
|

Profiling N-Type Dopants in Silicon

Abstract: Variously doped n-type structures (dopant concentration between 1:5 Ã 10 16 cm À3 and 1:5 Ã 10 19 cm À3 ) on a lightly doped p-type silicon substrate (doped to 1:9 Ã 10 15 cm À3 ) have been examined by a photoemission electron microscope equipped with a high-pass energy filter and by an ultra-high vacuum scanning low energy electron microscope. High contrast have been observed between the n-type areas and the p-type substrate and its monotone dependency on the doping level of structures has been manifested. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The photoemission electron microscopy study produced a proposal to explain the observed phenomena with p/n differences in absorption of the hot electrons on their move toward the surface, existing due to a different energy threshold for generation of the e-h pairs [ 48 ]. The first detailed study of the n-type patterns on the p-type substrate [ 49 ] produced data previously not available, which we discuss below.…”
Section: Resultsmentioning
confidence: 99%
“…The photoemission electron microscopy study produced a proposal to explain the observed phenomena with p/n differences in absorption of the hot electrons on their move toward the surface, existing due to a different energy threshold for generation of the e-h pairs [ 48 ]. The first detailed study of the n-type patterns on the p-type substrate [ 49 ] produced data previously not available, which we discuss below.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Similar results can be found in the work presented by Venables et al [50] and Xu et al [20] Hovorka et al employed photo emission electron microscopy (PEEM) as a more sensitive alternative to the SEM and probing the surface energy spectra for Si with different dopant concentrations with its mechanism of hot electron generation. [55] Heath et al applied external bias and varied the bias to calibrate the SE signal. [36] Hovorka et al and Heath et al are the only two cases found to successfully establish a monotonic dependency between the image intensity and the doping levels for Si with an n-type emitter.…”
Section: Semdci Issues With N-type Dopingmentioning
confidence: 99%
“…After non-zero diffracted rays emerge, flat surface crystals may be imaged in the diffraction contrast [8]. When varying the landing energy of electrons, we get doped areas in semiconductors revealing either a proportional dopant contrast or a constant brightness [9], [10].…”
mentioning
confidence: 99%